Exploring Talent And Interests Through The Harapan Foundation And The University Of Medan Area - Irwansyah Putra; Nurmaida Irawani Siregar; Dina Maizana (International Journal of Community Service Implementation, 2025)
The program "Exploring Talent and Interests through the Hope Foundation and the University of Medan Area" was created to address the challenges faced by students in identifying their potential and determining appropriate career paths. Many students struggle to recognize their interests and talents, making it difficult to choose between continuing education, entering the workforce, or becoming entrepreneurs after graduation. This issue underscores the need for structured guidance and support. The program, collaboration between the Hope Foundation, known for its focus on community empowerment, and the University of Medan Area, aims to provide students with a clear framework to explore and develop their talents. Through workshops, mentoring, and personalized feedback, students gain the necessary knowledge and skills to make informed decisions about their future. Quantitative data were collected through post-program surveys assessing participants' confidence levels, awareness of their skills, and preparedness for future career paths. Participants rated their experiences on a Likert scale ranging from 1 to 5, measuring aspects such as clarity in career direction and engagement with personal interests. Results from the program demonstrate that participants experienced increased confidence in recognizing their abilities and showed greater preparedness for professional and societal contributions. The combination of group discussions, aptitude tests, and mentor evaluations allowed students to objectively measure their progress. The program successfully provided a comprehensive approach to self-development, promoting stronger engagement with individual interests and talents.